2020
DOI: 10.29312/remexca.v11i8.2082
|View full text |Cite
|
Sign up to set email alerts
|

Disponibilidad de nitrógeno y rendimiento de biomasa de Ricinus communis L. fertilizado con biosólidos

Abstract: Un criterio para estimar la dosis de aplicación de biosólidos en suelos agrícolas es el nitrógeno disponible y el requerimiento del cultivo. El objetivo del estudio fue determinar la disponibilidad de nitrógeno de dos biosólidos generados a partir de sistemas de tratamiento diferente y su efecto sobre el rendimiento de aceite a partir de semilla de Ricinus communis L. Los tratamientos consistieron en tres fuentes de nitrógeno (N) y tres dosis, además de un testigo sin N. Las fuentes de N fueron: sulfato de amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
(13 reference statements)
0
2
0
Order By: Relevance
“…Some studies have reported that the addition of sewage sludge to the soil increases the productivity of the castor bean crop, resulting in high dry matter and seed oil yield (Capuani et al, 2015;Maciel-Torres et al, 2017). Cavalcanti et al (2015) reported that the productivity of castor bean fertilized with sewage sludge and potassium magnesium sulphate was similar to that found with NPK fertilization, indicating the potential of this residue as a substitute for mineral fertilization.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Some studies have reported that the addition of sewage sludge to the soil increases the productivity of the castor bean crop, resulting in high dry matter and seed oil yield (Capuani et al, 2015;Maciel-Torres et al, 2017). Cavalcanti et al (2015) reported that the productivity of castor bean fertilized with sewage sludge and potassium magnesium sulphate was similar to that found with NPK fertilization, indicating the potential of this residue as a substitute for mineral fertilization.…”
Section: Discussionmentioning
confidence: 95%
“…The benefits on the chemical and physical properties of soils are very evident and contribute to considerable increases in crop productivity (Alburquerque et al, 2015;Capuani et al, 2015;Cavalcanti et al, 2015;Áfaz et al, 2017;Maciel-Torres et al, 2017;Eid et al, 2018).…”
Section: Discussionmentioning
confidence: 99%